1996
DOI: 10.1115/1.2840936
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Performance of a High Work Research Turbine

Abstract: This paper describes the design and performance of a high work single-stage research turbine with a pressure ratio of 5.0, a stage loading of 2.2, and cooled stator and rotor. Tests were carried out in a cold flow rig and as part of a gas generator facility. The performance of the turbine was assessed, through measurements of reaction, rotor exit conditions and efficiency, with and without airfoil cooling. The measured cooled efficiency in the cold rig was 79.9 percent, which, after correcting for temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Moustapha et al [7] (Highly Loaded Turbine) showed the effect of blade loading on high loaded ( H /U 2 = 2.4) stage efficiency at off-design conditions; increase in the rotor blade loading by 53 per cent reduced the efficiency by 2.5 per cent. Vlasic et al [8] (High Work Research Turbine) investigated a single-stage turbine with a pressure ratio of 5 and stage loading of 2.2, the efficiency is reduced by 2.1 per cent when the turbine-cooling rate goes from 0 to 11 per cent. Woinowsky-Krieger et al [9] showed that a 10 per cent reduction in the rotational speed resulted in a decrease of 3 per cent in the efficiency for a single-stage transonic turbine.…”
Section: Introductionmentioning
confidence: 99%
“…Moustapha et al [7] (Highly Loaded Turbine) showed the effect of blade loading on high loaded ( H /U 2 = 2.4) stage efficiency at off-design conditions; increase in the rotor blade loading by 53 per cent reduced the efficiency by 2.5 per cent. Vlasic et al [8] (High Work Research Turbine) investigated a single-stage turbine with a pressure ratio of 5 and stage loading of 2.2, the efficiency is reduced by 2.1 per cent when the turbine-cooling rate goes from 0 to 11 per cent. Woinowsky-Krieger et al [9] showed that a 10 per cent reduction in the rotational speed resulted in a decrease of 3 per cent in the efficiency for a single-stage transonic turbine.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, a number of other investigations considered the influence of blade cooling on shock wave loss. Bohn et al, 19 Vlasic et al 20 investigated losses downstream of transonic airfoils with trailing edge ejection. They found that the pressure at base region arises because of trailing edge ejection.…”
Section: Introductionmentioning
confidence: 99%
“…Bohn et al., 19 Vlasic et al. 20 investigated losses downstream of transonic airfoils with trailing edge ejection. They found that the pressure at base region arises because of trailing edge ejection.…”
Section: Introductionmentioning
confidence: 99%